Outcomes of resections that spare vs remove an MRI-normal hippocampus - Morita-Sherman, Marcia; Louis, Shreya; Vegh, Deborah; Busch, Robyn M.; Ferguson, Lisa; Bingaman, Justin; Bulacio, Juan; Najm, Imad; Jones, Stephen; Zajichek, Alexander; Hogue, Olivia; Kattan, Michael W.; et al. (Epilepsia, 2020)
Objective: To characterize seizure and cognitive outcomes of sparing vs removing an magnetic resonance imaging (MRI)–normal hippocampus in patients with temporal lobe epilepsy. Methods: In this retrospective cohort study, we reviewed clinical, imaging, surgical, and histopathological data on 152 individuals with temporal lobe epilepsy and nonlesional hippocampi categorized into hippocampus-spared (n = 74) or hippocampus-resected (n = 78). Extra-hippocampal lesions were allowed. Pre- and postoperative cognitive data were available on 86 patients. Predictors of seizure and cognitive outcomes were identified using Cox-proportional hazard modeling followed by treatment-specific model reduction according to Akaike information criterion, and built into an online risk calculator. Results: Seizures recurred in 40% within one postoperative year, and in 63% within six postoperative years. Male gender (P =.03), longer epilepsy duration (P <.01), normal MRI (P =.04), invasive evaluation (P =.02), and acute postoperative seizures (P <.01) were associated with a higher risk of recurrence. We found no significant difference in postoperative seizure freedom rates at 5 years between those whose hippocampus was spared and those whose hippocampus was resected (P =.17). Seizure outcome models built with pre- and postoperative data had bootstrap validated concordance indices of 0.65 and 0.72. The dominant hippocampus-spared group had lower rates of decline in verbal memory (39% vs 70%; P =.03) and naming (41% vs 79%; P =.01) compared to the hippocampus-resected group. Partial hippocampus sparing had the same risk of verbal memory decline as for complete removal. Significance: Sparing or removing an MRI-normal hippocampus yielded similar long-term seizure outcome. A more conservative approach, sparing the hippocampus, only partially shields patients from postoperative cognitive deficits. Risk calculators are provided to facilitate clinical counseling.
CRIS-Team Scopus Importer:2020-10-23
Keywords: epilepsy surgery; memory outcome; neuropsychological assessment; temporal lobe epilepsy